Neural pathways from hypothalamic orexin neurons to the ventrolateral preoptic area mediate sleep impairments induced by conditioned fear - Ma, Caifen; Zhou, Ning; Ma, Kang; Niu, Jiandong; Mi, Ting; He, Zhenquan; Wen, Yujun; Liu, Chunhong; He, Zhongyi; Niu, Jianguo (Frontiers in Neuroscience, 2023)
Introduction Fear and sleep impairments common co-exist, but the underlying mechanisms remain unclear. Hypothalamic orexinergic neurons are involved in the regulation of sleep-wake and fear expression. The ventrolateral preoptic area (VLPO) is an essential brain region to promote sleep, and orexinergic axonal fibers projecting to the VLPO are involved in the maintenance of sleep-wake. Neural pathways from hypothalamic orexin neurons to the VLPO might mediate sleep impairments induced by conditioned fear. Methods To verify above hypothesis, electroencephalogram (EEG) and electromyogram (EMG) were recorded for analysis of sleep-wake states before and 24 h after conditioned fear training. The retrograde tracing technique and immunofluorescence staining was used to identify the projections from the hypothalamic orexin neurons to the VLPO and to observe their activation in mice with conditioned fear. Moreover, optogenetic activation or inhibition of hypothalamic orexin-VLPO pathways was performed to observe whether the sleep-wake can be regulated in mice with conditioned fear. Finally, orexin-A and orexin receptor antagonist was administered into the VLPO to certify the function of hypothalamic orexin-VLPO pathways on mediating sleep impairments induced by conditioned fear. Results It was found that there was a significant decrease in the non-rapid eye movement (NREM) and rapid eye movement (REM) sleep time and a significant increase in the wakefulness time in mice with conditioned fear. The results of retrograde tracing technique and immunofluorescence staining showed that hypothalamic orexin neurons projected to the VLPO and observed the CTB labeled orexin neurons were significantly activated (c-Fos+) in the hypothalamus in mice with conditioned fear. Optogenetic activation of hypothalamic orexin to the VLPO neural pathways significantly decreased NREM and REM sleep time and increased wakefulness time in mice with conditioned fear. A significant decrease in NREM and REM sleep time and an increase in wakefulness time were observed after the injection of orexin-A into the VLPO, and the effects of orexin-A in the VLPO were blocked by a pre-administrated dual orexin antagonist (DORA). Conclusion These findings suggest that the neural pathways from hypothalamic orexinergic neurons to the VLPO mediate sleep impairments induced by conditioned fear.